Effect of graphene oxide loading in GO/SiO2/Ag/AgCl photocatalyst. (2017) - Granbohm, Henrika; Singh, Vivek K.; Ge, Yanling; Hannula, Simo-Pekka
In the presented work, Ag/AgCl decorated silica nanoparticles were introduced over graphene oxide (GO) sheets to prepare GO/SiO2 /Ag/AgCl nanocomposite powders for absorption and photocatalytic application. Nanocomposite powders were synthesised by sol-gel method and then characterised by various analytical techniques including X-ray diffraction (XRD), scanning electron microscopy and transmission electron microscopy. The amount of GO in nanocomposites was varied from 1 wt.% to 50 wt.% to investigate the role of graphene oxide on the absorption and photocatalytic properties of the nanocomposites. The photocatalytic activity of the GO/SiO2 /Ag/AgCl nanocomposites was examined under UV light taking methylene blue (MB) as a model dye.